MOTIVASI DAN BEBAN KERJA SEBAGAI PENENTU KINERJA KARYAWAN DI RSIA SELARAS CIKUPA - Candra, Adi; Gunawan, Weka; Hilmy, Reza (UI Scholars Hub, 2022)
Employee performance in an institution shows the successful implementation of all organizational activities. However, RSIA Selaras Cikupa, through initial observations found many problems related to performance, namely the number of employees who were late from January to June 2019 tended to increase every month. From the initial interviews it is also known that the low motivation of employees. The research objective was to determine the effect of motivation and workload on employee performance at RSIA Selaras Cikupa with job satisfaction as an intervening variable. This type of research is quantitative research. The method used is a survey with interval weighting. The number of samples in this study were 83 people. Analysis using multiple linear regression analysis. The results showed that there was a positive and significant influence between motivation and job satisfaction, there was a positive and significant effect between workload and job satisfaction, there was a positive and significant effect between job satisfaction and performance. In addition, motivation and workload simultaneously or simultaneously have a significant effect on performance variables at RSIA Selaras Cikupa. The most dominant variable is work motivation variable.